“Fail to Scale“: The persistent Problem of Technology Transfer and Possible Solutions Based on Key Agroecological Principles - Frija, Aymen (International Center for Agricultural Research in the Dry Areas, 2023)
Plenary presentation on “Fail to Scale: The persistent Problem of Technology Transfer and Possible Solutions Based on Key Agroecological Principles” – delivered on October 11th. This communication occurred during the 20th International Scientific Day of INRGREF in Tunis, Tunisia “Sustainable Ecosystem Management for Agroecological Transition and Food Security” (10-11 October 2023).